Desidratação de polpa de manga e suco de caju integral por atomização e caracterização dos produtos obtidos - Rocha, Érica Milô de Freitas Felipe (2013)
The main aim of the study was to obtain powder of whole mango pulp and whole cashew juice by drying in a Spray-dryer. Innitially, it was made as assessment of all conditions in the process related to the output and humidity of those powders through experimental designs such as complete rotational central compound. From the results were produced powder of mango and cashew which underwent a physical-chemical and hygroscopic characterization, being analyzed the following parameters: water activity, humidity, pH, soluble solids, acidity, vitamin C, carotenoids, total and reducing sugars, colorimetric parameters (L *, a *, b *, C * and h0), hygroscopicity, degree of caking, rehydration and sorption isotherms. The samples produced by this drying process presented good quality both physicochemical and hygroscopic and, for the parameter sorption isotherms, both the powders (mango and cashew), presented as the type III (Format J) which characterizes the foods with high sugar content, and the model of Henderson, at all temperatures which were analyzed, was the best that fit. Next, were evaluated the stability of these powders in storage period of 180 days under two different packages (laminated and transparent). Thus, it was concluded that, after this storage period, both mango and cashew powder enclosed in those different packages, still were in the form of powder with good physico-chemical and hygroscopic characteristics, being the laminated packaging the one which best showed the barrier protection to the samples.